Research of the Nutrition Problem: Methodological Approaches and Daily Practices - A. V. Noskova (Vestnik MGIMO-Universiteta)
The article analyzes some scientific approaches to nutrition research and current nutrition practices for students of two Moscow Universities. The author notes that the necessity for scientific studying of food has been understood at the end of the XIX - the beginning of the XX centuries. In the article the social context of three directions of researches of a nutrition problem is analyzed: natural-scientific, ethnographic and sociological. The answer to a question why the healthy nutrition for modern society is an actual problem is given. It is shown that modern social transformations have changed sociocultural regulation of nutrition consumption. The variety of scientific approaches to food is revealed: a food as a factor of physical health, a food as an ethnocultural tradition, a food as a social habit and marker of the social status of the individual. The special emphasis is made on the European sociology of food. In the last thirty years in this area, some special sociological theories were formed: sociology of nutrition, sociology of food, sociology of menu, etc. Consumer abundance in modern western society changed a view of sociologists on essence and functions of food. New social factors give now more pressure on the nutrition practices. Based on food diaries and essays of 60 Moscow students, the author's project shows and analyzes the current nutrition practices of youth. The analysis of some peculiarities in the youth choice of food is made. The influence of social/dietary/religious norms on food behavior of students is shown. Value of "healthy food" in youth interpretation is shown. In the end of the article, the author notes the dialectics of freedom / social pressure for nutrition practices of modern youth.